PEMBUATAN LEMBAR KERJA PESERTA DIDIK (LKPD) FISIKA SMA KELAS X BERORIENTASI STRATEGI PEMECAHAN MASALAH IDEAL - Syafwan Syafwan; Mahrizal Mahrizal; Zulhendri Kamus (Universitas Negeri Padang, 2016)
Teachers need some supporting elements to achieve goals of learning process such as teaching materials and learning strategy. In fact, several units such as the scope, procedure, and focus of teaching materials for each unit still needed to be developed. This research was expected to contribute for increasing students’ competence. One of the supporting elements was students’ Physics worksheet (LKPD) of Senior High School grade X which oriented on IDEAL problem solving strategy. This strategy consisted of five steps, such as identify the problem, define the problem, explore solution, act on the strategy, look back and evaluate the effect (IDEAL). The type of this research was research and development with four-D model which was define, design, develops and disseminate steps. The research was conducted until develop step because disseminate step had some limitedness. The product of this research was examined for validity, practicality, and effectiveness. Validity test was conducted by Drs. Asrul, M.A, Drs. Gusnedi, M.Si, Dra. Murtiani, M.Pd, Drs. Amali Putra, M.Pd and Drs. Masril, M.Si, as Physics Lectures at State University of Padang. After validated by lecturers, the product was applied at X Science 2 at SMAN 1 Padang to determine its practicality and effectiveness. Practicality test was conducted by 3 teachers and 21 students of SMAN 1 Padang using questioners. Based on data analysis, there were three research results. First, LKPD of Senior High School grade X which oriented on IDEAL problem solving strategy was very valid with 82.58. Second, the results of limited applying showed that LKPD of Senior High School grade X which oriented on IDEAL problem solving strategy was very practical with 80, 02 and effective used in teaching learning process. Third, the students’ knowledge competence was increased